Influence of molybdenum tailings by-products as fine aggregates on mechanical properties and microstructure of concrete. (15th August 2022) - Quan, Xiaoyi; Wang, Sheliang; Liu, Kangning; Xu, Jin; Zhao, Nan; Liu, Bo
Abstract: The disposal of industrial by-product tailings has become a key part of the mining follow-up and an important issue in solving environmental pollution. This study investigated the possibility of using molybdenum tailings (MTs) as fine aggregates in concrete production. Based on the concept of full-scale recycling, the replacement ratio of MTs was set to 0%, 20%, 40%, 60%, 80%, and 100%. Firstly, the mechanical properties (compressive and splitting tensile strengths) of concrete with different MTs replacement ratios were investigated at different curing ages (14, 28, 56, and 90 days). Then the pore structure characteristics were explored based on nuclear magnetic resonance (NMR) non-destructive testing techniques. Subsequently, the spatial model of the pore structure was obtained and the porosity information was extracted from the 3D reconstruction by industrial computed tomography (CT). The relationship between porosity, pore size distribution, and compressive strength ( f cu ) was established. Finally, the cost and environmental impacts (EI) of concrete with different MTs replacement rates were evaluated. The experimental results show that the mixed fine aggregate of MTs and natural sand is very suitable for concrete preparation at the appropriate replacement ratio of MTs. Although the f cu and splitting tensile strengths ( f sts ) of concrete decreased with the increase of the proportion of MTs. The mechanical properties of concrete with 60% MTs decreased by less than 10% compared with no MTs added. The porosity of MTs concrete is negatively correlated with the f cu . The pore size distribution also has a significant effect on the f cu . Pores with pore size >1000 μm had a negative and significant effect on the f cu . The cost and EI assessment further demonstrated that using 60% MTs to replace natural fine aggregates in concrete applications is the best reuse option to develop energy efficient and environmentally friendly concrete. Highlights: A molybdenum tailings by-product is used as fine aggregate in the development of concrete. Nuclear magnetic resonance to analyze the pore structure characteristics is adopted. Industrial CT to observe the evolution of the 3D pore structure and distribution are conducted. The relationship between compressive strength and pore distribution was established. Economic and environmental assessments were used for further validation.